Functional components of carob fruit: linking the chemical and biological space - Goulas, Vlasios; Stylos, Evgenios; Chatziathanasiadou, Maria V.; Mavromoustakos, Thomas; Tzakos, Andreas G. (My University, 2016)
The contribution of natural products to the drug-discovery pipeline has been remarkable since they have served as a rich source for drug development and discovery. Natural products have adapted, during the course of evolution, optimum chemical scaffolds against a wide variety of diseases, including cancer and diabetes. Advances in high-throughput screening assays, assisted by the continuous development on the instrumentation’s capabilities and omics, have resulted in charting a large chemical and biological space of drug-like compounds, originating from natural sources. Herein, we attempt to integrate the information on the chemical composition and the associated biological impact of carob fruit in regards to human health. The beneficial and health-promoting effects of carob along with the clinical trials and the drug formulations derived from carob’s natural components are presented in this review.
Keywords: Cancer; Carob; Diabetes; Diarrhea; Fiber; Hyperlipidemia; Locust bean gum; Omics; Polyphenols; Tannins